The Violations of Politeness Principle In Hate Speech By Haters To Barbie Kumalasari As The Actrees of Indonesia In Youtube Comments - Rini Afrilesa J (Jurnal Ilmiah Langue and Parole, 2021)
YouTube is a video sharing website that is growing rapidly among the public. Children to adults love to watch YouTube. They can freely search for any videos they want. Comment pages are also available for those who want to provide responses to the video. Sometimes comments from netizens are not only positive but can also be negative. Negative comments are given in the form of hate speech. In understanding of the hate speech an understanding of the context is needed. Pragmatics is a language science that talks about context. Context is very closely related to politeness. The hate speech is utterances that violate the rules of politeness. The using of hate speech by the Barbie Kumalasari’s haters proved to violate of politeness principle. The purpose of this study was to describe the form of violation of politeness principle carried out by the Barbie Kumalasari haters. Data was obtained from comments of YouTube channel netizens on the Rumpi No Secret program which featured Barbie Kumalasari as a guest star. This research is qualitative research that use pragmatic discourse analysis. There are several forms the violations of politeness principle performed by the haters of Barbie Kumalasari including: approbation maxim and agreement maxim.